Relationships between Nonlinear Viscoelastic Behavior and Rheological, Sensory and Oral Processing Behavior of Commercial Cheese. Issue 4 (11th March 2013) - Melito, H.S.; Daubert, C.R.; Foegeding, E.A.
Abstract Cheese texture is primarily determined by its structure. Structural differences can significantly alter rheological, sensory and oral processing behaviors. Large amplitude oscillatory testing (LAOS) has been used to study nonlinear viscoelastic properties of gels, which were related to sensory and oral processing characteristics. Therefore, nonlinear viscoelastic properties of several types of commercial cheese were measured and correlated with rheological, sensory and oral processing characteristics to determine the relationships among these characteristics for more complex food systems. Cheddar, Mozzarella and American cheese were selected for evaluation. Cheddar displayed the greatest degree of nonlinear behavior under LAOS; American cheese displayed the least. Rheological, sensory and oral processing evaluation revealed significant (α = 0.05) differences in behavior of the different cheese. Correlations were found between nonlinear viscoelastic, rheological, sensory and oral processing behaviors. Thus, LAOS testing may be used to gain insight into solid food structure and structural breakdown, yielding additional information on textural properties. Practical Applications This work extends the use of large amplitude oscillatory shear (LAOS) to real food systems, showing the applicability of this technique to a variety of materials. In addition, LAOS may be used to test foods with a range of textures, from liquids to semisolids to soft solids. Using LAOS to measure the nonlinear viscoelastic properties of foods allows nonlinear behavior to be quantified in foods that cannot be tested with traditional large‐strain rheology due to sample limitations. The nonlinear viscoelastic properties may be used to make inferences on texture and breakdown of food during mastication.